Class Repertoire sebagai Strategi Pembelajaran Mata Kuliah Musik Media dalam Memahami Mood Musik Film - Pandan Pareanom Purwacandra; Febri, I Wayan Nain; Setiarini, Agnes Tika (Pusat Riset dan Inovasi Nasional, 2025)
This research examines the effectiveness of using a repertoire class as a learning strategy in the Media Music course of the Film and Television Production Study Program at the Indonesian Institute of the Arts, Yogyakarta. The course, offered in the fourth semester, focuses on film music creation, mood development, and instrumental understanding. The study applies the Classroom Action Research method with the primary goal of improving students’ comprehension of film scoring components. Pre-cycle findings showed that students’ understanding was relatively low under previous teaching approaches. To address this, the repertoire class method was introduced. This strategy emphasises active learning through sound samples from various instruments, allowing students to directly experience and analyse how musical elements shape the mood of a film. The interactive design of this method provides not only theoretical insights but also practical, auditory experiences that deepen learning. The research was carried out in three CAR cycles, each evaluating student progress and adjusting strategies as needed. Results demonstrate a notable improvement in learning outcomes. The percentage of students achieving Excellent and Very Good categories increased significantly, while the number in the Poor category decreased. These findings confirm that repertoire classes, especially those incorporating instrumental sound samples, are highly effective in enhancing students’ understanding of the emotional dimension of film music. In conclusion, this approach enriches the learning experience and equips students with both technical knowledge and emotional sensitivity in film scoring. By integrating practice-based methods, the repertoire class proves to be a valuable strategy in media music education.